Faktor-Faktor Kinerja Keuangan Dan Karekteristik Perusahaan Terhadap Harga Saham Perusahaan Lq-45 - Mohammad Aryo Arifin (Universitas PGRI Palembang, 2017)
The main objective of this study is to analyze the influence of total cash flow, profit, and financial leverage to stock price. The sample use in this study are LQ-45 companies listed in indonesia stock exchange in the period of 2013- 2017. The analytical techniuqe of this study uses multiple regression method to examine the relantionship between variables. The results of this study indicate that simultaneously the total cash flow, profit, and financial leverage significantly influence the stock price. Partially the total cash flow do not affect the stock price, profit indicate positive significance to stock price, while the financial leverage indicate negative significance to stock price.Key Words : Total Cash Flow, Profit, Financial Leverage, and Stock Price